Reproducibility of heart rate recovery measures across differing modalities and intensities of submaximal exercise in healthy volunteers: A healthy volunteer study - Haroon Minhas; Christopher Morton; Martin Shaw; Ben Shelley (Anesthesiology and Perioperative Science, 2024)
Abstract Purpose Submaximal exercise tests (SET) are an easier to conduct and less physically demanding alternative to cardiopulmonary exercise testing for assessment of pre-operative fitness. Assessment of heart rate recovery (HRR) following SETs offers an easily obtained marker of vagal reactivation and sympathetic withdrawal and therefore provides an indication of an individual’s fitness. This study sought to assess the reproducibility of HRR across different workloads and modalities of SET. Methods Thirty-four healthy volunteers were recruited to undergo two SETs at 40% and 60% of their predicted maximal workload. A second group of thirty-one healthy volunteers were recruited to undergo three SETs of differing modalities; Cycle ergometry, Step and Shuttle Walk tests. HRR was quantified using the conventional indices HRR1 and HRR2 (calculated as heart rate (HR) on exercise cessation minus HR at 1 and 2 min of rest) and a novel area under the HRR vs. time curve (HRRAUC) method. Reproducibility of results was assessed using intra-class correlation coefficient (ICC) and limits of agreements. Results The results showed that HRR1 and HRR2 were poorly reproducible across differing workloads and exercise modalities (ICC < 0.45 for all comparisons) whereas HRRAUC proved to be at least moderately reproducible (ICC > 0.52 for all comparisons). Conclusions These results suggest that HRRAUC may be a superior way of quantifying HRR following SETs, adding objectivity to SET results. Quantifying HRRAUC could prove to have useful clinical applications for pre-operative risk assessment, assessing fitness to undergo treatment and monitoring disease progression.